Individual differences in L2 frequency effects in different script bilinguals. (August 2020) - Mor, Billy; Prior, Anat
Aims: High frequency words are read more quickly and accurately than low frequency words, a phenomenon called the frequency effect. In the current study, we examine several possible predictors for explaining individual differences between bilinguals in their sensitivity to frequency in the second language: specific second language exposure and vocabulary; general language abilities (therefore also evident in native language performance); and general cognitive ability (non-linguistic sensitivity to regularities). Approach: We used an individual differences approach with unbalanced Hebrew–English bilinguals, two typologically different languages that do not share a writing system, which allows a clear discrimination between native language and second language exposure and vocabulary. Data and analysis: To examine frequency effects, 69 Hebrew–English bilingual adults completed lexical decision tasks in native language and second language. In addition, participants completed vocabulary tests in both languages, reported language use and proficiency, and performed a statistical learning task. Data were analyzed using linear mixed-effects models. Findings: The results demonstrated that only vocabulary knowledge in the second language was a significant predictor of frequency effects in the second language. In addition, neither sensitivity to frequency in the native language nor statistical learning ability (a measure of general sensitivity to regularities) predicted sensitivity to frequency in the second language. Originality: Using an individual differences approach with bilinguals of two typologically different languages that do not share a writing system allows us to distinguish between native language and second language proficiency, and therefore identify the unique contribution of predictive factors from each of the languages to efficient visual word recognition in second language. Implications: The current findings support the lexical entrenchment hypothesis and highlight the importance of testing a variety of bilingual populations.